2016
DOI: 10.1002/anie.201510148
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State NMR of PEGylated Proteins

Abstract: PEGylated proteins are widely used in biomedicine but, in spite of their importance, no atomic-level information is available since they are generally resistant to structural characterization approaches. PEGylated proteins are shown here to yield highly resolved solid-state NMR spectra, which allows assessment of the structural integrity of proteins when PEGylated for therapeutic or diagnostic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 53 publications
5
46
0
Order By: Relevance
“…As already observed in the case of PEGylation, [30] these signals correspond to the amide groups generated by functionalization of the e-amino group of lysines (H z -N z )w ith the MenC polysaccharide moieties.T he resonances of the non-functionalized lysines would appear at very low 15 Nchemical shift values (around 30 ppm), but are usually wiped out by exchange.O nt he contrary,w hen they become amides,e xchange is slowed down and the intrinsic flexibility of the sidechain justifies the appearance of the H z -N z cross-peaks.T hese signals are markers that can provide direct information on the number of lysine residues involved in the formation of new bonds with the MenC polysaccharide. However,t he assignment of each H z -N z couple to the corresponding H-N of the backbone is adifficult task because of the high overlap between H z -N z signals,a nd the lack of connections between the two H-N couples across the side chain.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…As already observed in the case of PEGylation, [30] these signals correspond to the amide groups generated by functionalization of the e-amino group of lysines (H z -N z )w ith the MenC polysaccharide moieties.T he resonances of the non-functionalized lysines would appear at very low 15 Nchemical shift values (around 30 ppm), but are usually wiped out by exchange.O nt he contrary,w hen they become amides,e xchange is slowed down and the intrinsic flexibility of the sidechain justifies the appearance of the H z -N z cross-peaks.T hese signals are markers that can provide direct information on the number of lysine residues involved in the formation of new bonds with the MenC polysaccharide. However,t he assignment of each H z -N z couple to the corresponding H-N of the backbone is adifficult task because of the high overlap between H z -N z signals,a nd the lack of connections between the two H-N couples across the side chain.…”
supporting
confidence: 58%
“…[27] However,a lso for mass spectrometry the evaluation of the conjugation degree at the different sites in polydisperse populations of isomers is ac hallenge.R ecently,w eh ave shown that structural information on large PEGylated proteins,s uch as E. coli l-Asparaginase-II (138 kDa, ANSII, see the Supporting Information), can be obtained by solid-state NMR spectroscopy. [30] Several excellent reports on capsular polysaccharides,b acterial cell walls and their maturation have been obtained by the same technique. [31][32][33] ANSII is not used as carrier protein in glycoconjugate vaccines,h owever,i ty ields highly resolved SSNMR spectra, [30] and approximately 74 %o ft he resonances have been assigned (unpublished data).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of NMR of sedimented solutes [69][70][71] has lifted the needs for crystallization in the case of soluble proteins, yielding access to soluble but non-crystallizing targets such as PEGylated proteins [130]. However, as seen by NMR, biomaterials are complex entities: the protein and the inorganic matrix interplay to define physicochemical characteristics of the composite, in terms of mobility, hydration, etc.…”
Section: Biomaterials From the Nmr Standpointmentioning
confidence: 99%